1988
DOI: 10.21273/jashs.113.6.864
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-coated Urea as a Slow-release Nitrogen Source for Onions

Abstract: Field studies with onions (Allium cepa L. cv Monarch) were conducted in 1980 and 1981 to compare preplant-banded sulfur-coated urea (SCU) with preplant-banded and split applications of urea. Treatments were evaluated at two N rates, 56 and 224 kg·ha−1. Root NO3-N and soil NO3-N concentrations in bed centers indicated slower release of N from SCU than from urea. Nevertheless, total and large bulb (> 76 mm in diameter) yields and N uptake in onion bulbs and leaves from SCU were significantly higher under low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the NPK treatments, N uptake in the bulb was higher in the 3-split application than in the single application while C, N, P K, S, Ca and Mg contents in the leaf were higher in the single application than in the 3-split application. Brown et al (1988) reported that increased yields with sulfur-coated urea compared to pre-plant urea at low N application rates, but not at high application rates. In their study, the high application rate exceeded total N uptake by approximately 100 kg ha -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the NPK treatments, N uptake in the bulb was higher in the 3-split application than in the single application while C, N, P K, S, Ca and Mg contents in the leaf were higher in the single application than in the 3-split application. Brown et al (1988) reported that increased yields with sulfur-coated urea compared to pre-plant urea at low N application rates, but not at high application rates. In their study, the high application rate exceeded total N uptake by approximately 100 kg ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…The CRFs are expected to be most effective in conditions to accelerate mineralization of nutrients such as excessive rainfall or irrigation (Morgan et al, 2009). Onion bulb yields increased with sulfur-coated urea compared to pre-plant urea at low N application rates, but not at high application rates (Brown et al, 1988). In their study, high application rate exceeded total N uptake by approximately 100 kg ha -1 , indicating the high N application rate was excessive.…”
Section: Introductionmentioning
confidence: 93%
“…Later research found that preplant SCU often produced yields equal to that produced in treatments receiving split applications of soluble N (Brown et al, 1988), especially in conditions where nutrient leaching was a concern (Waddell et al, 1999(Waddell et al, , 2000. For example, when SCU was applied to potato (Solanum tuberosum) as a single application 1 month after planting, yield of potato from SCU-treated plots was equal to that obtained from urea-treated plots in 2 of 3 years (Liegel and Walsh, 1976).…”
Section: Materials That Are Slow Release Due To Reactionmentioning
confidence: 99%